La captura y almacenamiento de carbono: una novedosa técnica de reducción de emisiones de gases de efecto invernadero regulada por la Unión Europea - Sanz Rubiles, Íñigo (2013)
This article deals with main aspects of a novel technique for carbon dioxide capture and storage released by large combustion plants. Since this novel technique has become essential for reducing greenhouse gas emissions, it has been regulated by the European Union through the Directive number 2009/31. Therefore, acknowledging relevant legal aspects for regulation, suchas: mandatory, exploration permits, storage among others, the focus has been pointed out on responsibilities and guarantees regime.